Survey of Apicultural Practices in Ibadan, Oyo State, Nigeria (2020)
Apiculture is the practice and management of the bees in the hive with the sole aim of producing honey and other products including bee wax, propolis, bee-venom and royal jelly. Apiculture forms a line of productions that makes up agribusiness, but with challenges along the production chain. Little or no work has been done on the activities of beekeepers and the economic benefits of beekeeping in the study area. Therefore, the study aimed to assess the apicultural practices of beekeepers in Ibadan, Oyo State, Nigeria. Structured questionnaires were administered to the beekeepers and honey marketers in three Local Government Areas (Akinyele, Ibadan North and Ibadan South East), purposively selected. The questionnaires comprise of two sections: demographics characteristics and apicultural practices of the respondents. The snowball sampling technique was used to select 30 beekeepers from the three Local Government Areas in the study areas. Data collected were analyzed using descriptive statistics such as mean, frequency table and percentage distribution. The results of the study revealed that 96.7% were male dominated, within the age bracket (36.7%) and mostly married (76.7%). About 63.3% of the beekeepers use bee product as baiting material. At harvesting period, 80.0% of the respondents employ modern smoker for driving away bees while 56.7% stores honey in plastic as it provides suitable conditions for honey preservation. In line with their high education level, 86.7% of the respondents embrace modern beekeeping because of its being less tedious but with maximum output. Requiring low capital, modern beekeeping allows people an increased income resulting in improved standard of living. Many of the respondents, however, faced the problem of theft and bee sting,thus women were reluctant in practicing beekeeping as a means of livelihood. The paper recommended better security against thieves and more training on proper bee handling to minimize bee sting to encourage more people embrace the business with the hope of improved productivity.